RELIABILITY STUDY OF OPERATORS WITHIN A COMPLEX ERGATIC SYSTEM: RELIABILITY STUDY OF OPERATORS WITHIN A COMPLEX ERGATIC SYSTEM - Getzov, Petar; Hubenova, Zoya (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The article examines the UAV operator reliability and possibility of transferring the theory of reliability concepts of technical objects to the activities of individuals and groups. Structural information analysis of the human operator activity controlling an UAV has been carried out taking into account the ground complex information structure. An assessment of the reliability criteria of the operator for accuracy and timeliness has been made.